Policy and Practices of E-Waste Management in Nepal: An Emerging Challenge - Pantha, Rewoti Ram; Pianroj, Yutthapong; Techato, Kuaanan; Gyawali, Saroj (Journal of Lumbini Engineering College, 2023)
E-waste management is an immediate matter of concern for every country of the world as it not only pollutes the environment but also very toxic and hazardous to the health of living beings. Major challenges to its management come from lack of understanding of the scope and depth of the management methods, legislation relating to e-waste and socio-economic issues of the country. These challenges can be resolved only if public-private partnership goes hand in hand with knowledge of the consequences of improper disposal practices. The reuse and recycle of e-waste is to be disseminated backed by the proper Regulatory Framework.